Effects of general anaesthesia during pregnancy on neurocognitive development of the fetus: a systematic review and meta-analysis. (June 2021) - Bleeser, Tom; Van Der Veeken, Lennart; Fieuws, Steffen; Devroe, Sarah; Van de Velde, Marc; Deprest, Jan; Rex, Steffen
Abstract: Background: The US Food and Drug Administration warned that exposure of pregnant women to general anaesthetics may impair fetal brain development. This review systematically evaluates the evidence underlying this warning. Methods: PubMed, EMBASE, and Web of Science were searched from inception until April 3, 2020. Preclinical and clinical studies were eligible. Exclusion criteria included case reports, in vitro models, chronic exposures, and exposure only during delivery. Meta-analyses were performed on standardised mean differences. The primary outcome was overall effect on learning/memory. Secondary outcomes included markers of neuronal injury (apoptosis, synapse formation, neurone density, and proliferation) and subgroup analyses. Results: There were 65 preclinical studies included, whereas no clinical studies could be identified. Anaesthesia during pregnancy impaired learning and memory (standardised mean difference −1.16, 95% confidence interval −1.46 to −0.85) and resulted in neuronal injury in all experimental models, irrespective of the anaesthetic drugs and timing in pregnancy. Risk of bias was high in most studies. Rodents were the most frequently used animal species, although their brain development differs significantly from that in humans. In a minority of studies, anaesthesia was combined with surgery. Monitoring and strict control of physiological homeostasis were below preclinical and clinical standards in many studies. The duration and frequency of exposure and anaesthetic doses were often much higher than in clinical routine. Conclusion: Anaesthesia-induced neurotoxicity during pregnancy is a consistent finding in preclinical studies, but translation of these results to the clinical situation is limited by several factors. Clinical observational studies are needed. Prospero registration number: CRD42018115194